Bioinformatics research and applications : 10th International Symposium, ISBRA 2014, Zhangjiajie, China, June 28-30, 2014. Proceedings - Pan, Yi; Wang, Jianxin; Basu, Mitra (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 10th International Symposium on Bioinformatics Research and Applications, ISBRA 2014, held in Zhangjiajie, China, in June 2014. The 33 revised full papers and 31 one-page abstracts included in this volume were carefully reviewed and selected from 119 submissions. The papers cover a wide range of topics in bioinformatics and computational biology and their applications including the development of experimental or commercial systems.